Bone Infarct as an Indicator of Acute Spinal Ischaemia - Laura López-Viñas; Kary Leonisa Quiñones-Coneo; Raquel Buenache-Espartosa; Juan Salvador Martínez-; Gustavo Lorenzo-Sanz (Hindawi Limited, 2020)
Acute spinal cord infarct in childhood is extremely rare, generally secondary to spinal/cardiovascular surgery or severe vertebral injuries. However, spontaneous spinal cord infarct cases have been described. We present a clinical case of a teenager who developed an acute weakness and paraesthesia in lower limbs after playing piggyback. Laboratory tests and MRI (magnetic resonance imaging) were normal. During her hospital admission, her motor strength improved. After 10 days, MRI was repeated, and a bone infarct was observed. She was medicated with acetylsalicylic acid, and she completed a rehabilitation program.